Literasi Kitab Kuning pada Santri Pondok Pesantren Al-Muhsinin Desa Koto Petai Kabupaten Kerinci - Maisaroh, Dian (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2020)
ABSTRACT Introduction. The purpose of this study was to determine the ability of the students of the Al-Muhsinin Islamic Boarding School in Koto Petai Village to access, evaluate, and use information on the kitab kuning content with literacy standards of the International Federation of Library Association and Institutions (IFLA).Data Collection Method. To collect precise and accurate data, the researcher used qualitative research. The method of determining the subject was done by purposive sampling, the data collection methods used were the interview method, the observation method and the documentation method.Analysis Data. Data analysis was used, namely data reduction, data presentation, and drawing conclusions.Results and Discussions. The results of this study are: The ability of the Santri at the Al-Muhsinin Islamic Boarding School of the Koto Petai Village in Accessing Information on the Kitab Kuning is quite good, this can be seen from the information obtained from discussions with teachers and clerics and also with friends. and chosen to be applicable in everyday life. The ability of the Santri at the Al-Muhsinin Islamic Boarding School of Koto Petai Village in Evaluating Information on the Kitab Kuning is quite good, it can be seen that to get clear information each person has different versions, some select and sort the information first and some are direct use the information. It depends on each person how to get the information. The ability of the Santri at Al-Muhsinin Koto Petai Islamic Boarding School in using the Kitab Kuning information is not good. It can be seen that in using the information obtained by the informants they have not applied or applied it and in communicating information to other parties, the informants also rarely communicate the information they know to other parties. Keywords: Information Literacy, Kitab Kuning, Santri